Dinuclear Silver(I) Nitrate Complexes with Bridging Bisphosphinomethanes: Argentophilicity and Luminescence - Kristina F. Baranova; Aleksei A. Titov; Oleg A. Filippov; Alexander F. Smol’yakov; Alexey A. Averin; Elena S. Shubina (Crystals, 2020)
Two silver nitrate complexes with bisphosphines were obtained and characterized: [Ag(dcypm)]2(NO3)2 (1; dcypm = bis(dicyclohexylphosphino)methane) and [Ag(dppm)]2(Me2PzH)n(NO3)2 (n = 1, 2a; n = 2, 2b; dppm = bis(diphenylphosphino)methane, Me2PzH = 3,5-dimethylpyrazole). The steric repulsions of bulky cyclohexyl substituents prevent additional ligand coordination to the silver atoms in 1. Compounds obtained feature the bimetallic eight-member cyclic core [AgPCP]2. The intramolecular argenthophilic interaction (d(Ag···Ag) = 2.981 Å) was observed in complex 1. In contrast, the coordination of pyrazole led to the elongation of Ag···Ag distance to 3.218(1) Å in 2a and 3.520 Å in 2b. Complexes 1 and 2a possess phosphorescence both in the solution and solid state. Time-dependent density-functional theory (TD-DFT) calculations demonstrate the origin of their different emission profile. In the case of 1, upon excitation, the electron leaves the Ag–P bonding orbital and locates on the intramolecular Ag···Ag bond (metal-centered character). Complex 2a at room temperature exhibits a phosphorescence originating from the 3(M + LP+N)LPhCT state. At 77 K, the photoluminescence spectrum of complex 2a shows two bands of two different characters: 3(M + LP+N)LPhCT and 3LCPh transitions. The contribution of Ag atoms to the excited state in both complexes 2a and 2b decreased relative to 1 in agreement with the structural changes caused by pyrazole coordination.